Pengaruh Kepuasan Kerja, Motivasi, dan Kedisiplinan Terhadap Produktivitas Kerja Karyawan PT. Sinarmas Multifinance di Surakarta - Mayasari, Ratih; Hendratmoko, Christiawan (STIE Surakarta, 2013)
This research was carried out on PT. Sinarmas Multifinance in Surakarta. The aim of the study are: (1) To know the influence of work satisfaction, motivation, and discipline toward productivity. (2) To know the dominant factor among work satisfaction, motivation, and discipline that influence toward productivity. The hypothesis drawnare: (1) Presummed that there are influence of work satisfaction, motivation, and discipline toward productivity. (2) Presummed that motivation has dominant influence toward productivity. The population of this research is 49 employees of PT. Sinarmas Multifinance in Surakartawith primary data. Technique of Analysis applied are validity test, reliability test, multiple linear regression, t-test , F- test and coefficient of determination. The results of this study are: (1) There are simultaneous and significant influence of work satisfaction, motivation, and discipline toward productivity. (2) Motivation has dominant influence toward productivity in PT. Sinarmas Multifinance, Surakarta